Analysing the maritime network of the port of Algeciras Bay. (16th May 2020) - Ansorena, Iñigo L.
Algeciras Bay is located at the Gibraltar Strait, a chokepoint of the world's main sea routes. The port of Algeciras plays a key role in the western Mediterranean area and this paper aims to shed new light on its maritime network. First, we use a clustering approach (the Louvain method) to reveal well connected groups of ports. Then in the second stage, we analyse centralities to determine ports with a special position. The Algeciras network exhibits a scale-free structure (a few dominant ports with many connections and a large number of ports with few connections). We also find six groups of well-connected ports and strong correlations between centrality measures and frequency of nodes. Our findings are important not only from the perspective of shipping companies interested in the design of regular services, but also from the perspective of the port of Algeciras Bay. The Port Authority can use the outcomes of the research to strengthen cooperation with the most relevant ports in the network via twinning agreements.